PENGARUH EDUKASI TERHADAP TINGKAT PENGETAHUAN DAN PERILAKU MASYARAKAT TENTANG DAGUSIBU ANTIBIOTIK DI KURNIA SELATAN SUNGAI RUMBAI - Ita Dwiaini (Nusantara Hasana Journal, 2022)
Antibiotics are drug used to treat infectious disease caused by bacteria. The high incidence of infectious disease results in a high use of antibiotics. There are still mamy antibiotics obtained whitout a doctor’s prescription, even though antibiotics must be purchased by a doctor’s prescription. Education is an effort to avoid undesirable things such as antibiotics resistence, so, education can increase public knowledge and awareness in Koto Bakti Kurnia Selatan, Sungai Rumbai district, west Sumatra which uses antibiotics. This study aims to determine to what extent the level of community knowledge and behavior regarding how to use drugs properly and correctyly and to determine the effect of education on knowledge of antibiotics dagusibu by using a Quasy research design experiment with pre-test post-test control group design approach to 31 control groups and 36 intervention groups by door to door method. The result of the research before the interventions, it turns out that there are still people who get antibiotics without a doctor’s prescription, use antibiotics for diseases other than infections, store medicines in the refrigerator, and throw medicines directly into the trash box. After interventions, the results obtained in the interventions group increased 52% experience and 10% control group with a good level of knowledge. So, that there is a significant difference in the level of knowledge and behavior of respondents before and after education, as evidenced by p value = 0,000 (p≤ 0,05).